Outcome analysis of liver stiffness by ARFI (acoustic radiation force impulse) elastometry in patients with chronic viral hepatitis B and C - Görtz, Rüdiger; Sturm, Jörg; Zopf, Steffen; Wildner, D.; Neurath, Markus; Strobel, Deike (Clinical Radiology, 2014)
To evaluate the association between liver stiffness measured by acoustic radiation force impulse (ARFI) elastometry and the outcome of antiviral treatment in patients with chronic viral hepatitis B and C.Thirty-eight patients with chronic viral hepatitis B (n = 16) or hepatitis C (n = 22) underwent liver biopsy and ARFI elastometry of the right hepatic lobe. A follow-up assessment using ARFI was performed a mean of 2.3 years after the baseline evaluation. The patients with favourable outcome were classified in group S and those receiving no treatment, showing no response to treatment, or experiencing a relapse were classified in group N.The 38 patients had an initial mean ARFI value of 1.56 ± 0.62 m/s as compared with 1.54 ± 0.64 m/s in the follow-up evaluation. Group S showed a significant decline in ARFI values (1.55 ± 0.60 m/s versus 1.34 ± 0.47 m/s; p < 0.05) and included 16 (64%) patients with lower shear wave velocities at follow-up. In group N, liver stiffness values showed a slight but not significant increase (1.57 ± 0.70 m/s versus 1.93 ± 0.77 m/s).Changes in liver stiffness during antiviral therapy can be assessed by ARFI reflecting response or no response. ARFI elastometry is an additional, useful tool for the follow-up assessment of treatment outcome in patients with chronic viral hepatitis B or C infection.
EVALuna2:1862